2014
DOI: 10.1017/s0022215113003484
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of vestibular vertigo in a neuro-otology clinic population in Thailand

Abstract: This study provides current data on the epidemiology of vestibular vertigo in a Thai neuro-otology out-patient population. The results include data on the prevalence of the new diagnostic entity of vestibular migraine, and on its association with potential triggers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The prevalence of VM in previous studies was dependent on different diagnostic criteria and study populations. Prior to the current diagnostic criteria, the prevalence of VM was 9%-11.9% in headache clinics, 4.7%-29.3% in otolaryngology clinics, and 6%-25.1% in specialized dizziness clinics (4,11,14,19,20,23). Only one study assessed the prevalence of VM based on the consensus criteria formulated by the Barany Society and the IHS; 4.2% were assigned to the definite VM group and 5.7% to the probable VM group in a tertiary referral otolaryngology clinic (12).…”
Section: The Prevalence Of Vmmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of VM in previous studies was dependent on different diagnostic criteria and study populations. Prior to the current diagnostic criteria, the prevalence of VM was 9%-11.9% in headache clinics, 4.7%-29.3% in otolaryngology clinics, and 6%-25.1% in specialized dizziness clinics (4,11,14,19,20,23). Only one study assessed the prevalence of VM based on the consensus criteria formulated by the Barany Society and the IHS; 4.2% were assigned to the definite VM group and 5.7% to the probable VM group in a tertiary referral otolaryngology clinic (12).…”
Section: The Prevalence Of Vmmentioning
confidence: 99%
“…Many illnesses, such as Me´nie`re's disease, somatoform vertigo, benign paroxysmal positional vertigo, transient ischemic attacks, syncope and orthostatic hypotension, vestibular paroxysmia, and episodic ataxia type 2 can cause vertigo or dizziness in patients with migraine (6)(7)(8). Among these, vestibular migraine (VM) or migrainous vertigo is recognized as a frequent and important cause of recurrent vertigo in patients with or without migraine (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of VM varies according to the different diagnostic criteria and study populations used; its prevalence is reported in the range of 4.3–29.3%, while the prevalence of probable VM is 4–5.7% [4, 5, 1315]. Prior to the publication of the current diagnostic criteria, the rates of VM were reported to be 4.2–29.3% in otolaryngology clinics, 6–25.1% in specialized dizziness clinics [4, 5, 1316], and 9–11.9% in headache clinics [5, 17].…”
Section: Epidemiology Of Vmmentioning
confidence: 99%
“…The diagnostic algorithm presented helps to unravel the complexities of differential diagnoses in this patient population. 5 Interventions for sudden sensorineural hearing loss remain controversial. The initial publications on corticosteroid use and attempts to define a 'responder' that is different from natural recovery continue.…”
mentioning
confidence: 99%